Profile Of Assertive Behavior of Students Participating in The Youth Red Cross Organization (PMR) (Qualitative Descriptive Study of SMA Negeri 16 Padang - Himami, Nuri Kaspil (Lembaga Riset Mutiara Akbar, 2022)
This research is motivated by members of the juvenile red cross (PMR) who should have assertive nature, but in fact there are still many students who follow the youth red cross who do not have that assertive nature. Students who find it difficult to communicate what will be conveyed. The purpose of this research is 1) students have the ability to be honest and direct. 2) students are open, what they are and able to act in their interests. 3) students are able to take the initiative for their interests. 4) students are willing to ask for information and help from others when needed and help when others need help. 5) students in dealing with conflicts can adjust and find solutions. 6) students have self-satisfaction, self-esteem, and self-confidence. This research was conducted using qualitative descriptive method. The research informants were 2 students as key informants and 4 students as additional informants using observation and interview data collection techniques. Meanwhile, data analysis was carried out systematically. Based on the results of research on the assertive behavior profile of students who follow the Youth Red Cross Organization (PMR) (a qualitative descriptive study of SMA Negeri 16 Padang) it can be concluded: 1) students have the ability to be honest and direct. 2) students are open, what they are and able to act in their interests. 3) students are able to take the initiative for their interests. 4) students are willing to ask for information and help from others. 5) students in dealing with conflicts can adjust and find solutions. 6) students have self-satisfaction, self-esteem, and self-confidence. This research is recommended to students so that students can grow and have assertive behavior.